Effect of the Reaction Temperature on the Optical Properties of CdSTe Quantum Dots Synthesized Under Microwave Irradiation. Issue 30 (28th July 2016) - Rivera-Rodriguez, Glorimar; Peralez-Perez, Oscar; Su, Yi-Feng; Alamo-Nole, Luis
ABSTRACT: Water-stable CdSTe quantum dots were synthesized under microwave irradiation heating conditions. An aqueous telluride solution (produced by reducing metallic Te with NaBH4 ), cadmium sulphate and thioglycolic acid were mixed together in an oxygen-free atmosphere to prevent oxidation of the telluride species. The reaction temperature varied from 60° C to 180° C and was controlled by using a microwave reactor (1, 000 W) to control nucleation rate and tune the size of the quantum dots. Photoluminescence analyses of resulting quantum dots evidenced a red shift (from 490 nm to 640 nm, using an excitation wavelength of 380 nm) when the reaction temperature was increased, which suggested crystal growth. The variation in size was also evidenced by the color of the quantum dot suspensions that changed from blue to red, when excited with a 405 nm, 5mW diode laser. The highest quantum yield was observed for quantum dots synthesized from 120° to 150° C. X-ray diffraction analyses suggested the formation of a solid solution of CdSTe with average crystallite size ranging from 1.4 nm to 3.2 nm. FT-IR spectroscopy evidenced the presence of residual thioglycolic functional groups onto the crystals surface, whereas HRTEM confirmed the nanometric size of the quantum dots.